Pengembangan Bahan Ajar Materi Teks Negosiasi Berbantuan Aplikasi Anyflip pada Siswa Kelas X SMA Swasta Gajah Mada Medan - Maria Kezia Trifosa Haryadi; M. Oky Fardian Gafari (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research aims to: (1) describe the process of developing teaching materials for negotiation text materials assisted by the Anyflip application for class Mada Medan. The research and development model used is ADDIE with five stages, namely analysis, design, development, implementation and evaluation. The instruments used were interviews, as well as material validation questionnaires, design validation, and responses from Indonesian language study teachers. Data were analyzed using qualitative descriptive and quantitative descriptive analysis techniques (Likert scale). The results of the research and development carried out are teaching material products for negotiation text materials assisted by the Anyflip application with good average assessment results.